Strength and microstructure of micro ceramic dust admixed lime stabilized soil - James, Jijo; Pandian, Pitchai Kasinatha (Revista de la Construcción. Journal of Construction, 2018)
The use of micro ceramic dust (CD) as an additive to lime in soil stabilization has been analysed in this study. CD was obtained by crushing and sieving of waste ceramic tiles from construction debris. The initial consumption of lime (ICL) for soil modification was determined using Eades and Grim pH test. In order to study the effect of lime content on soil stabilization, three different lime contents (below ICL, ICL and above ICL) were used for stabilizing the soil. These three lime contents were amended with various amounts of CD to study its effect on the strength of the stabilized soil. Unconfined compression strength (UCS) tests were carried out on the stabilized soil specimens of dimensions 38mm x 76mm at different ages of curing. The spent UCS samples were crushed and sieved to carry out Atterberg limits and free swell tests followed by x-ray diffraction (XRD) and scanning electron microscopy (SEM) tests for determining changes in microstructure. The results indicated that the addition of CD resulted in a marginally negative influence on the early strength of the stabilized soil at three days of curing whereas it enhanced the delayed strength of the soil at 28 days of curing, gaining between 12-14% strength. The effect of CD on the plasticity and swell-shrink of lime stabilized soil indicated a further reduction in plasticity and swell-shrink nature. The mineralogy of the amended soil revealed the formation of CSH and CAH minerals responsible for strength gain. SEM images used to analyse the microstructure of the virgin and stabilized soil, indicated the formation of a dense and compact microstructure. Finally, it was concluded that CD can be adopted as an auxiliary additive to lime in stabilization of expansive soil with provision of sufficient curing and the delayed onset of early strength due to CD can be overcome by using higher lime content in stabilization.